Spectral correlation of synthesized ethyl-4-(subs. phenyl)-6-methyl-2-oxo (or thio)-1, 2, 3, 4-tetrahydropyrimidine-5-carboxylate - Halim, Md Ershad; Khan, M N; Shaha, U; Rahman, M H; Akhter, K; Ahmed, S M (Bangladesh Journal of Scientific and Industrial Research, 2024)
Urea or thiourea, ethyl acetoacetate, and substituted aromatic aldehydes were combined in a one-pot Biginelli coupling reaction to create a few 1, 2, 3, 4-tetrahydro pyrimidine-5-carboxylate derivatives without any unsafe organic solvent. The catalyst used for this reaction was nickel nitrate hexahydrate [Ni(NO3)2.6(H2O)]. The elemental analyses, mass spectral data, 1H-NMR, 13C-NMR, UV, and IR were used to characterize the separated pure products. Bangladesh J. Sci. Ind. Res. 59(4), 223-230, 2024